FUMIGASI ARSIP STANDAR DAN PROSEDUR PELAKSANAAN FUMIGASI ARSIP: Array - Riko Priyatmo (Arsip Nasional Republik Indonesia, 2017)
This study attempted to develop technical protection of archives especially for the paper-based archives and encounter the challenges on conducting a good and proper fumigation for the archives. This is a descriptive qualitative research. The data collection method is done by using primary and secondary data. Most of the archive institutions and creating agencies fumigate their archives every year as one of the efforts to preserve their archives from insects and other materials that can damage the archives. However, these institutions are still not aware on how to fumigate their archives properly. Basically, in order to fumigate the archives, these institutions have to refer to the safety standards and procedures for Human and environment that include materials, tools, certified human resources or fumigators .and also the formal steps on fumigating the archives.